Canada's Crisis in Arctic Science: The Urgent Need for an Arctic Science and Technology Policy; Or, "Why Work in the Arctic? No One Lives There" - England, John H.; Dyke, Arthur S.; Henry, Gregory H.R. (ARCTIC, 1998)
Canada has entered a deep crisis in Arctic science. The lack of a formal Arctic Science and Technology Policy has left our highly fragmented efforts in Arctic research exceedingly vulnerable during times of financial stress and left us effectively without a voice. Logistical support, essential for operating in our vast northern territory, has all but disappeared as a facilitator for both government and university research. Within two years, only specially funded research will be possible, and opportunities for new careers will continue to plummet. The Arctic science community must alert the government to take action. If nothing is done to secure its future, Canada's capacity to perform Arctic research will collapse. . We speak here as active Arctic scientists who are alarmed by the rapid and continuing erosion of northern research in Canada, and who wish to highlight this crisis, draw instructive contrasts with recent U.S. initiatives, and offer, for discussion, a possible solution in light of current Canadian circumstances. Our essay seeks to make it clear that, if corrective action is not taken, Canadian Arctic science will shrivel to insignificance.